Effectiveness of Mindfulness Training on Problem Solving between Elementary Girl Students in Fifth Grade - Somayeh Pourmohamadi; Fariborz Bagheri (Kurdistan University of Medical Scienses, 2014)
Objective:The purpose of this research was to investigate the effectiveness of mindfulness training on problem solving between elementary girl students in fifth grade. Method: The research method was quasi experimental design (two groups with pre-test and post-test) and the statistical population consisted of all elementary girl students in fifth grade in Six Educational Zone in Tehran, from whom 24 students were selected by convenience sampling and then were assigned to experimental group (n=12) and control group (n=12). All students in the experimental and the control groups had taken computer based London Tower Test. Then, the experimental group participated in 12 sessions of mindfulness training, the combination of general mindfulness training for children and executive mindfulness training in American elementary school (Kaiser-Greenland, 2010) modeled based on MBCT-C (mindfulness-based cognitive therapy-children) Baer’s protocol (2006), over a 8 weeks period. Data were analyzed using ANCOVA on SPSS 18 software. Results: Results of this study showed that the two groups of experimental and control were significantly different in problem solving (P<0.05) abilities.